No Time for Modesty; Is Anyone Watching?; Are You Experiencing Burnout? ; Public Relations: Editors Rate Pillsbury, ADA and DAY Top PR Operations - Jim Shaner; Linda Benedict (Journal of Applied Communications, 1986)
Reviews of "No Time for Modesty," by Kirk A. Astroth and Benny S. Robbins; "Is Anyone Watching?" by Mary Beth Lang, Kristine L. Blacklock, and Boyd E. Rossing; "Are You Experiencing Burnout?" by O. Chris Igodan and L.H. Newcomb; "Public Relations: Editors Rate Pillsbury, ADA and DAY Top PR Operations," by Dick Elfenbein.